Women's Empowerment in Fisheries and Aquaculture Index (WEFI): Guidance Notes - McDougall, Cynthia; Kruijssen, Froukje; Sproule, Katie; Serfilippi, Elena; Rajaratnam, Surendran; Newton, Julie; Adam, Rahma (WorldFish, 2022)
WorldFish, KIT and other partners have created the Women's Empowerment in Fisheries and Aquaculture Index (WEFI) guidance notes and accompanied tools. WEFI measures the empowerment, agency and inclusion of women in fisheries and aquaculture contexts in an effort to identify ways to overcome those obstacles and constraints. The index content and themes have been inspired by the Women's Empowerment in Agriculture Index (WEFI). It has the quantitative component (the index) and a qualitative component.